Development of a TB Treatment Compliance Instrument using the Health Belief Model - Aminuddin, Aminuddin; Collein, Irsanty; Ismunandar, Ismunandar (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Several things that influence patient non-compliance in undergoing treatment include the length of treatment, in addition, there are drug factors, diseases and patients.Another fact is the lack of attention from the government and the patients themselves because even though free treatment is available. Aim of the study was to compile a TBC medication complient instrumen. The method using surveyThe sample was TB patients in Palu City, namely at the Talise Health Center, and in Donggala Regency, namely the Wani Health Center and the Gonenggati Donggala Health Center. The sample that participated in this study was 69 people. The analysis technique used was multidimensional confirmatory factor analysis (SEM). 20 question items were obtained from this study. Compliance questionnaires using the health belief model can be used to measure TB patient compliance with treatment. consisting of 3 assessment items; perceived benefit, perceived threat, perception of seriousness and threat. Compliance questionnaires using the health belief model can be used to measure TB patient compliance with treatment.